FORMULATION OF PSEUDOMONAS FLUORESCENS AS A BIOPESTICIDE AGAINST SOIL BORNE ROOT PATHOGENS - & et al., Al-Waily (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Pseudomonas fluorescens is one of the most beneficial rhizosphere bacteria mostly used to control broad range of soil borne plant pathogens. The local isolate of P.fluorescens (PFDS) was formulated using calcium carbonate (CaCo3), starch, grind rice and grind hornwort (Ceratophylum demersum L.)  as carriers to examine the best carrier for application of bacteria to control the  plant pathogenic fungi Fusarium solani and Rhizoctonia solani and root-knot nematode Meloidogyne javanica. The results revealed a significant superiority of starch and CaCo3 (35.3, 32.3 Î107 CFU ml-1) respectively compare to the other carriers with no significant differences among them, with nearly similar pattern of viability along six months of storage at room temperature (8.66, 8, 6.66, 4.33, 4.33 and 2 Î109 CFU ml-1) and (4.66, 4.66, 5, 4.33, 3.66 and 2.33 Î109 CFU ml-1) respectively. The monthly test showed that CaCo3- P.fluorescens formulation was represented high inhibition in vitro to the radial growth of F.solani (81.48, 79.26, 80.66, 80.31, 79.2 and 55.55 %) respectively and R.solani (74.07, 73.33, 72.22, 70.37, 66.66, and 44.44%) respectively along six months of storage with significant differences among treatments of each group. CaCo3 formulation at a concentration of 5 gm l-1 reduced in vitro eggs hatching to 5% and 44% death of the 2nd stage juvenile of M.javanica.